POTENTIAL REALIZATION OF PERENNIAL SORGHUM SEED PRODUCTIVITY AT “AGROSTYMULIN”APPLICATION - D’omin, D.; Kulyk, M.; Myhno, Yu. (Scientific Progress & Innovations, 2021)
In order to ensure high economic effectiveness of agriculture in Ukraine, the development of the energy sector, along with food security, is also of high importance. This requires a comprehensive, in-depth study and introduction of plant energy resource into production. The study of ways to increase the biomass yields of energy crops at their cultivation on marginal lands is important as well. This envisages their agronomical justified cultivation and the use of phytomass. Perennial sorghum or Columbus grass (Sorghum Almum Parodi) is the most adapted to the growing conditions and highly productive among energy crops. It is also important to increase the seed yield of the crop to ensure a sufficient supply of seed material for new energy plants. The aim of our research was to determine the effect of “Agrostymulin” application on the seed yield of perennial sorghum. General and special (experimental) methods were used in the research. According to the approved methods, we determined the quantitative plant indicators and seed yield measurements. Significant differences and correlations between the experimental variants were identified on the basis of variance and correlation analyses. The research results made it possible to define the variability of plant biometric indicators and reveal the impact of “Agrostymulin” complex application on the peculiarities of perennial sorghum seed yield formation. It was determined that the duration of the growing season during all three years was within the range of 122–132 days. The complex application of the preparation enables to reduce its period, which is especially important in the early periods of plant growth and supports less weed infestation of young perennial sorghum plants. The use of “Agrostymulin” for seed treatment and foliar fertilization has the greatest impact on the height, density of stand and plant reproductive organs’ indicators. In general, over the years, a significant increase in seed yield (1.9 t/ha) was obtained on the variants with complex “Agrostymulin” application, which significantly exceeded the control (by 0.5 t/ha). The prospects for further research will consist in identifying the ways to improve seed quality of sorghum crops in order to increase the sowing suitability of seed material of energy crops.